Big Data Mining approach to E-governance: Mining Census data for enhanced citizen centric policy making (International Journal of Engineering and Computer Science, 2017)
With Internet and technology making exponential rise in its presence in recent years, the role of public has increased in governments across the states or country and the people are becoming more aware about policies being made by the government and expressing their views about them, suggesting improvement and expressing happiness about good policies. When it comes to policy making, it is influenced by multiple factors, the policies must be made keeping the masses in mind, and assessing its impact on the masses, a policy can be termed as being a good one, if and only if it is benefiting the masses. The process of policy making will become easy and the policies would turn out to be of more benefit and help the masses if it they are made after taking into consideration the needs and requirements, which can be done if we have enough data to analyze which is in sufficient magnitude to reflect the current status of the citizens of the country. It’s not a challenge to get the data, but it would be huge in size and challenge will be in analyzing it. As humans can’t analyze such amounts of data, Data Mining comes to rescue here, the data can be collected and mined on various parameters to understand the current state, the citizens of the country are and hence policies can be made which would directly reflect in nations progress